Keep Calm and Carry On: The Relations Between Narrative Coherence, Trauma, Social Support, Psychological Well-Being, and Cortisol Responses - Vanaken, Lauranne; Smeets, Tom; Bijttebier, Patricia; Hermans, Dirk (Frontiers in Psychology, 2021)
In order to explain trauma resilience, previous research has been investigating possible risk and protective factors, both on an individual and a contextual level. In this experimental study, we examined narrative coherence and social support in relation to trauma resilience. Participants were asked to write about a turning point memory, after which they did the Maastricht Acute Stress Test, our lab analogue of a traumatic event. Following, half of the participants received social support, whereas the other half did not. Afterwards, all participants wrote a narrative on the traumatic event. Moment-to-moment fluctuations in psychological and physiological well-being throughout the experiment were investigated with state anxiety questionnaires and cortisol measures. Results showed that narratives of traumatic experiences were less coherent than narratives of turning point memories. However, contrary to our predictions, coherence, and in particular thematic coherence, related positively to anxiety levels. Possibly, particular types of thematic coherence are a non-adaptive form of coping, which reflect unfinished attempts at meaning-making and are more similar to continuous rumination than to arriving at a resolution. Furthermore, coherence at baseline could not buffer against the impact of trauma on anxiety levels in this study. Contrary to our hypotheses, social support did not have the intended beneficial effects on coherence, neither on well-being. Multiple explanations as to why our support manipulation remained ineffective are suggested. Remarkably, lower cortisol levels at baseline and after writing about the turning point memory predicted higher coherence in the trauma narratives. This may suggest that the ability to remain calm in difficult situations does relate to the ability to cope adaptively with future difficult experiences. Clinical and social implications of the present findings are discussed and future research recommendations on the relations between narrative coherence, social support and trauma resilience are addressed.